Огляд стану та можливостей поліпшення організації комутаційних процесів у силових трансформаторно-ключових вузлах - Халіков, В.А. (Технічна електродинаміка, 2012)
They are considered with the general position condition, prospects and possibility of the improvement of the technical facilities to organizations and control connecting process at switching’s in power transformer-key nodes of the systems of the power electronics. Call attention about need of the use of software programs of visual simulation modeling of the processes, particularly in a part of the use the possibilities of the programme package MATLAB/Simulink. The measures are offered on minimization or eliminating the extreme manifestations, which can accompany the processes.